Фольклорные мифы в древних тюркских памятниках - B.S.Sarbasov, B.D Zhumakaeva (Eurasian Journal of Philology Science and Education, 2018)
Turkic monuments of folk myths is one of the important issues in the field of literature. Because, today, is still not complete with research. The former is based on the daily lite of our ancestors to keer the literatury and artistic techniques. Surrounding natural phenomena: the sun, moon, earth, stars, etc, phenomena considered holy mountain. Satellite lmages of people at one time early mythical notion soon became a regular artist in a poetic oral. This research article is mainly Turkic monuments folk myths zeriitewlerime analysis they determined that it was importans. Still valuable things were not expected in the near future.